2018
DOI: 10.3390/app8112156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Time of Isothermal Holding on Retained Austenite Stability in Medium-Mn Steels

Abstract: Effects of isothermal holding time and temperature on the stability of retained austenite in medium manganese bainitic steels with and without Nb microaddition were investigated. The amount of retained austenite for various variants of thermomechanical processing was determined by X-ray diffraction. Relationships between processing conditions and microstructure were revealed using light microscopy and scanning electron microscopy techniques. The isothermal holding temperatures changed from 500 to 300 °C and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
(55 reference statements)
3
19
0
Order By: Relevance
“…The present steels show a continuous yielding behavior as a result of the mobile dislocations generated during previous thermomechanical processing. This was shown in our previous works [8,38]. Results obtained in the present study showed that the temperature factor has a significant influence on the PLC occurrence.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The present steels show a continuous yielding behavior as a result of the mobile dislocations generated during previous thermomechanical processing. This was shown in our previous works [8,38]. Results obtained in the present study showed that the temperature factor has a significant influence on the PLC occurrence.…”
Section: Discussionsupporting
confidence: 87%
“…The present steels show a continuous yielding behavior as a result of the mobile dislocations generated during previous thermomechanical processing. This was shown in our previous works [8,38]. So far, in the literature, there are only a few reports available concerning the PLC effect in medium manganese steels [14][15][16][17]21,24].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Subsequently, the sheet was continuously cooled to the bainitic transformation temperature and isothermally treated at 400 • C within 300 s. Finally, air cooling to room temperature was applied. Detailed information concerning the processing parameters can be found in work [21].…”
mentioning
confidence: 99%